Green Synthesis of ZnO Nanoparticles Using Prosopis fracta Extract with Two Solvents and Study of Their Biological Activities - Fakhree, Falah M; Mahmoud , Kamal M (International Journal of Psychosocial Rehabilitation, 2020)
The main goal of this paper is a green synthesis of zinc oxide nanoparticles with extracts of Prosopis fracta (growing in the Iraqi Kurdistan region) using two solvents, first with water (Zn-NPs-W) and second with methanol (Zn-NPs-M). The prepared nanoparticles characterizations were confirmed by UV-Vis absorption spectrophotometry; Fourier transforms infrared spectroscopy (FT-IR); scanning electron microscopy (SEM); X-ray Diffraction (XRD); and Transmission Electron Microscopy (TEM), in order to determine which solvent is more favorable in terms of particle size, particle agglomeration, and particle separation. The particle size of Zn-NPs-W was found to be 25 nm with a rod shape, while Zn-NPs-M had a particle size of 35 nm which is a wide range and gives a deformed rod shape. Further, it has been shown after testing the antibacterial activity of the two different sizes of the Zn-NPs (25, 35) nm against both gram-positive bacteria such as micrococcus species (M. species) Staphylo epidermidis (S.epidermidis); gram-negative such as Acinetobacter baumannii (A. baumannii), Pseudomonas aeruinosa (P. aeruinosa), and yeast Candida Albicans (C.albicans), with a different effect on bacteria. The most critical advantages of this process are the environmentally friendly and fast synthesis for both Zn-NPs-W and Zn NPs-M.